Hematological, Biochemical and Hemodynamic Changes during Operative Hysteroscopy using Consecutive Distension Media. Issue 1 (31st December 2023) - Mandour, Ahmed Mohamed; Elawamy, Abdelraheem; Abdelraouf, Abdelraouf M.S; Elsonbaty, Ahmed Mohamed; Elsonbaty, Mostafa; Darwish, Atef M; Abdalla, Esam; Hassan, Zein . Z; Anwar, Mohamed
ABSTRACT: Background: Hysteroscopy is a procedure for management of intrauterine pathology. Glycine 1.5% (200 mOsm/L) is one of the most commonly used distension media in hysteroscopy; but it carries risk of hypervolemia and dilutional hyponatremia. Objectives: Studying effects of systemic absorption of irrigating fluids on hemodynamic parameters, detect fluid deficit impact on clinical outcome included biochemical, hematological parameters, conscious level, pulmonary congestion and/or edema postoperative bleeding and hospital stay. Methods: Sixty patients ASA classes I & II aged between 20 and 40 years underwent elective operative hysteroscopy randomly assigned into two groups. The Study group (30 patients): where consequent saline 0.9% and glycine 1.5% were used as irrigating distension media. Control group (30 patients): where glycine 1.5% alone was used as a distension medium. Results: Comparing study and control group regarding (MBP) and heart rate, they were significantly higher at recovery and 6 hours postoperatively in the control group. (CVP) readings, showed significantly higher reading in the control group at times (15 m, 30 m, 45 m after induction, six hours and after recovery). Thoracic electrical bioimpedance parameters showed that COP, Cardiac index, Stroke volume and Stroke index were significantly higher in the control group than study group at 6 hours postoperatively. Regarding serum sodium, it was significantly lower in the control group than study group at times (15 min, 30 min and 45 min intra operatively) compared to pre-induction value. Serum osmolality was lower at 6 hours in the control group. Hemoglobin, hematocrit and platelet count was lower at 6 hours among control group. Conclusion: The sequential use of saline 0.9% and glycine 1.5% decreased the amount of absorbed glycine 1.5% and hence the related side effects and complications. Trial registration: Clinical Trials.gov. (NCT03166228)